WORK-FAMILY CONFLICT, SOCIAL SUPPORT AND MARRIAGE SATISFACTION ON EMPLOYEES AT BANK X - Juniarly, Amalia; Pratiwi, Marisya; Purnamasari, Ayu; Nadila, Tiara Fajria (Jurnal Psikologi, 2020)
This study aimed to determine the contribution of work-family conflict and social support in predicting marriage satisfaction. Eighty-seven female workers at Bank X who met the study's criteria, such as frontline worker, married with children; were involved in this study. The participants' age ranges from 22 to 45 years (M = 33.5; SD = 3.589). The researchers used the Work-family Conflict Scale (20 items, α = .879), the Social Support Scale (12 items, α = .927), and the Marriage Satisfaction Scale (38 items, α = .946). The data were analysed with multiple linear regression. The analysis results showed the value of R = .743; F(2, 84) = 51.652, p < .05, and it indicates that there is a significant role of work-family conflict and social support on marital satisfaction. Besides, a value of b = -.960, p < .05, was obtained, and it means that there is a significant role of work-family conflict on marital satisfaction and b = 1.209, p < .05 were found, meaning that there is a significant social support role on marriage satisfaction.